First Pierre Loti Day Meeting at Darülfünûn - Serkan Tuna (Skad)
Armistice Istanbul had one of the most important days with the first Pierre Loti Day meeting held in Darülfünûn Conference Hall on 23 January 1920. Purpose of the meeting which was organized by Pierre Loti Association founded on 10 January 1920 was to show the appreciation and thankfulness of Turkish Nation for Pierre Loti who was known as Turkophile. But also a national solidarity of Turkish Nation was aimed by this meeting too. Day of 23 January was admitted as Pierre Loti Day and to this end Istanbul media mentioned about him on the broadcast of those days by showing a big solidarity. Communities of 5.000 people including Crown Prince Abdülmecid Efendi, some deputies, government representatives, journalists and intellectuals and folks participated in the meeting. Especially the life and literary of Pierre Loti and his Turkish friendship was referred firstly on the meeting. Besides positive qualifications of Turkish Nation in the contexts of history was mentioned especially with the speech of Süleyman Nazif Bey whose speech caused debates. It’s possible to think this first Pierre Loti Day meeting as a successful civil society organization through which national solidarity was demonstrated.